Mycoplasma gallisepticum Infection and Efficacy of Inactivated Poultry Viral Vaccines - Marwa Fathy (Journal of Global Pharma Technology, 2019)
Objective: This study was designed to evaluate the effect of Mycoplasma gallisepticum (MG) infection on the antibody titers of viral vaccines in fourteen-day-old specific pathogen-free (SPF) chicks. Methods: Five types of inactivated poultry viral vaccines-Newcastle disease viral vaccine (NDVV), avian influenza viral vaccine (AIVV), infectious bronchitis viral vaccine (IBVV), infectious bursal disease viral vaccine (IBDVV) and Reo-Virus Vaccine were used to vaccinate five hundred chicks. The chicks were divided into twenty groups at the age of 14 days; five groups were infected with MG. At day twenty-one, all the groups were vaccinated (four groups for each vaccine one of them previously infected by MG and one simultaneously infected by MG). At day twenty-seven, five vaccinated non-infected groups were infected. Results: All pre-infected groups showed highest antibody titers against NDV, AIV, IBV, IBDV, and Reo V (7.4 log2, 7.1 log2, 20EU, 20EU, and 17EU, respectively) 28 days post-vaccination. The lowest titer appeared in non-infected vaccinated groups with NDV, AIV, IBV, IBDV, and Reo V (6.5 log2, 6.5 log2, 12EU, 14EU, and 11EU, respectively). Conclusion: This study highlighted the outcome of poultry vaccination with inactivated virus vaccines by using serological immune response especially in the presence or absence of Mycoplasma infection of chicks.Keywords: Mycoplasma gallisepticum, Poultry, Vaccine evaluation, SPF chicks, Serological immune response.